Digital Marketing Impacts for Preservation of Creative Culture in Aceh Study Case on Traditional Cakes Business - Azhari (Winaya Inspirasi Nusantara Foundation, 2022)
This study is a case study that comprehensively analyzes the phenomenon of digital marketing. The benefits of digital marketing use are felt by users. Business feels a dependence on digital marketing, including the business of Aceh's traditional cakes, especially in the era of the Industrial Revolution 4.0. The purpose of this study generally describes the impact of digital marketing on the preservation of traditional cakes in the city of Aceh Besar. This research is a qualitative type, using an interview method, in-depth interviews, and observations of business. The results of the study it is known that digital marketing makes it easy for society to preserve Aceh's traditional cakes, build a spirit to promote it to the people of the world, provides an opportunity to reach audiences with a wider scope and modern society, gives space to the young generation to know and love Aceh's traditional cakes, an increasing number of people who know Aceh’s culture.